2012
DOI: 10.4149/gpb_2012_042
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the fractional sarcoplasmic reticulum Ca2+ release in intact cardiomyocytes using integrated Ca2+ fluxes

Abstract: Abstract. The sarcoplasmic reticulum (SR) is the main source of contraction-activating Ca 2+ in the adult mammalian myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
0
7
0
7
Order By: Relevance
“…Cardiac myocytes were isolated with collagenase digestion using a previously described technique64. Briefly, the hearts were attached via the aorta to a cannula, excised and mounted in a Langendorff apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac myocytes were isolated with collagenase digestion using a previously described technique64. Briefly, the hearts were attached via the aorta to a cannula, excised and mounted in a Langendorff apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…The perfusion chamber containing the cells was placed on the stage of an inverted microscope (Nikon Diaphot 200) coupled to a microfluorimetry system (Photon Technology Intl, Inc.). The dye was excited at 360 nm, and the emission ratio at 410 and 485 nm was converted to [Ca 2+ ]i according to Bassani et al 64,. using calibration parameters determined in live cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend of increasing fractional Ca 2þ release, demonstrated by mES-CM cultured on scaffolds compared to mES-CM cultured in 2D suggests that a longer culture period on PVDF-TrFE scaffolds may promote fractional Ca 2þ release that is similar to native cardiomyocytes. It is shown that the physiological fractional Ca 2þ release of adult left ventricular rat cardiomyocytes is between 60% and 70% (Bassani et al, 2012). The increase in spontaneous contraction frequency in both mES-CM cultured in 2D and on PVDF-TrFE, with the treatment of isoproterenol, also suggests that these cells exhibit positive chronotropic responses to b-adrenergic stimulation, which is a hallmark of adult cardiomyocytes (He et al, 2003;Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, culture on PCL + G scaffolds promoted a significantly higher fractional release of approximately 40% compared to that of mES‐CM cultured in 2D (approximately 26%). Fractional release is an indicator of excitation‐contraction coupling efficiency and the fractional release of mature rat is approximately 60% . A higher fractional release further suggests that Ca 2+ handling function of mES‐CM is enhanced with culture on 3D graphene containing scaffolds.…”
Section: Discussionmentioning
confidence: 99%